Zinc Kinetics Correlate With Length-for-Age z Scores in Bangladeshi Infants. Issue 4 (15th July 2022) - Wastney, Meryl E.; Long, Julie M.; McDonald, Christine M.; Krebs, Nancy F.; Islam, M. Munirul; Ahmed, Tahmeed; Khandaker, Afsana Mim; Sthity, Rahvia Alam; Westcott, Jamie E.; King, Janet C.
Abstract : Objectives: Stunting [length-for-age z score (LAZ) <−2] has multiple causes and is prevalent in areas with low dietary zinc (Zn) intake. Zinc kinetics from non-stunted infants were used in a published model for predicting linear growth; here, we directly measure zinc kinetics in stunted infants. Methods: Zinc kinetics were determined in 9-month-old Bangladeshi infants (n = 10), who were non-wasted [weight-for-length z score (WLZ) > −2], ranging in LAZ from −2.9 to −0.43. Stable isotopes were administered 2 hours after a meal as oral ( 70 Zn) and intravenous ( 67 Zn) tracers. After isotope administration, blood was sampled within 5 hours and all urine and feces were collected for 24 hours. Urine was sampled twice-daily out to 9 days. Data were analyzed by compartmental modeling. Daily zinc intake was estimated by the model as the sum of zinc used for growth plus that lost via urine and feces. Zinc absorbed (the amount required to maintain steady state) was the sum of zinc used for growth plus urine and endogenous fecal excretions. Results: The LAZ score correlated with serum zinc concentration ( R = 0.77, P = 0.001), urinary zinc excretion ( R = 0.66, P = 0.010), and fractional zinc absorption from calculated daily intake ( R = 0.58, P = 0.030). In stunted infants (n = 8), the amount of zinc absorbed did not increase with calculated zinc intake unlike published values for non-stunted infants. Conclusions: Zinc kinetics in Bangladeshi infants correlate with LAZ and show that malabsorption of supplemental sources of zinc may occur in stunted infants.